Pemanfaatan Fitur Facebook Professional untuk Meningkatkan Literasi Digital Petani Desa Grujugan Lor Bondowoso - Fuad Nasir; Astrid Hidayanti Ananda Putri; Audha Fitrah Aulina (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2026)
This community service activity is driven by the low level of digital literacy among rural communities, particularly farmers in Grujugan Lor Village, Bondowoso Regency, which poses a major obstacle to optimizing agrotechnological adoption. Most farmers still rely on conventional methods and utilize the internet limitedly for entertainment. The purpose of this program is to enhance the digital literacy capacity of farmers by optimizing Facebook Professional (FB Pro) features as a medium for disseminating agricultural information and creating income opportunities. The implementation method involved a participatory workshop (comprising 30% theory and 70% hands-on practice) attended by the Women Farmers Group (KWT) of Grujugan Lor Village. The activity stages encompassed field surveys, partner coordination, module development, FB Pro account management simulation, and practice-based monitoring and evaluation. The monitoring and evaluation results showed a significant increase in participants' digital understanding and skills, demonstrated by their ability to independently configure accounts and produce engaging agrotechnological content. In conclusion, the workshop was successfully implemented; hence, continuous assistance from field extension officers is highly recommended to maintain consistency in agricultural content production by the partners.